EVALUATING INDONESIAN HERO STORIES FEATURED IN CHILDREN’S LITERATURE - Parlindungan, Firman; Rifai, Irfan; Nuthihar, Rahmad; Dewayani, Sofie (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This study delves into elementary school teachers’ evaluation of children’s books featuring Indonesian national heroes. Despite the significant roles of historical figures picturebooks, research on how teachers incorporate it as useful resources in teaching is limited. In fact, the availability of quality historical fiction picturebooks that portray stories of national heroes in Indonesia is also scarce. Through snowballing technique, 25 teachers voluntarily participated. Through an online questionnaire, they were asked to provide their opinion about three Indonesian hero storybooks, which include (1) Aku Kartini [I am Kartini], (2) Wahidin Soedirohoesodo Sang Dokter Bangsa [Wahidin Soedirohoesodo the Doctor of The Nation], and (3) Menyusuri Tempat Tinggal Srikandi Aceh Cut Nyak Meutia [Strolling the Residence of an Acehnese Heroine Cut Nyak Meutia]. The participants were asked to examine aspects like text complexity, plot, illustration, moral values, and pedagogical strategies for classroom implementation. The data were analyzed qualitatively to describe the teachers’ evaluation on the quality of the books. The findings emphasize the significance of continuous teachers’ professional development, especially in book selection and utilization. The consensus surrounding Book #1 “Aku Kartini” suggests its potential as a valuable resource for teaching national heroes, as well as a model of quality historical fiction picturebook. We argue that adult’s evaluation, particularly teachers, in selecting books for children to read, play a pivotal role both in the children and in the practice of teaching.